Implikasi Kegiatan Islah Manner dalam Penguatan Spiritualitas Siswa SDI Sahabat Berlian Laren - Maghfirotun, Khubni; Abid, Ainul; Azizah, Nur (IBTIDA’, 2025)
Islah manner activity is a mandatory activity which is one of the LCC (Learn, Custom, and Culture) programs at the Sahabat Berlian Islamic Elementary School. This reconciliation activity is carried out by children when they are about to face school exams. meet parents to apologize for all the mistakes and naughtiness that the child has done, ask for prayers and blessings so that every time he faces a test he will be given smoothness and success. So, based on this background, the researcher wants to conduct further research on the implications of the islah manner activity in strengthening the spirituality of students at SDI Sahabat Berlian Laren. This research is a case study research. The implications of the islah manner activity in strengthening the spirituality of SDI Sahabat Berlian Laren students are to create a good relationship with Allah SWT. Through Prayer and Fear of doing bad things. Good relationship with oneself (self-awareness and control) with a sense of peace and happiness, Doing tasks with focus and Accepting yourself Good relationships with others by having good relationships with friends and Parents pray for their children.